Miguel Calderón Campos: El español del reino de Granada en sus documentos (1492-1833). Oralidad y escritura (Berna: Peter Lang SA, 2015. 273 páginas) - Junquera, Macarena (Onomázein, 2017)
NO PRESENTA RESUMEN